Informing trial measurement in systemic lupus erythematosus: frequency of domain-specific disease activity in a multinational cohort - Tsutomu Takeuchi; Yoshiya Tanaka; Rangi Kandane-Rathnayake; Sang-Cheol Bae; Zhanguo Li; Shereen Oon; Vera Golder; Mandana Nikpour; Masayoshi Harigai; Yi-Hsing Chen; Zhuoli Zhang; Eric Morand; et al. (Lupus Science and Medicine)
Objective To report the prevalence of disease activity in individual SLE organ domains, including prevalence stratified by the most common disease activity cut-off score for clinical trial eligibility (SLE Disease Activity Index 2000; SLEDAI-2K ≥6).Methods We used data from a multinational longitudinal SLE cohort, prospectively collected between 2013 and 2020. Disease activity was categorised by the SLEDAI-2K into nine organ systems. We calculated proportions of organ-specific disease activity in the overall cohort and stratified by SLEDAI-2K ≥6 or <6, on both a per-patient and per-visit level.Results We included 4102 patients (92.0% female, 88.9% Asian) contributing 42 345 eligible visits. Serological disease activity was most prevalent, affecting 75.5% of patients at least once during follow-up, followed by renal (41.6%), cutaneous (36.5%), musculoskeletal (20.1%) and haematological (19.1%) activity. Serositis (3.4%), vasculitis (3.4%), central nervous system activity (3.0%) and fever (2.9%) occurred infrequently. In patient visits with an SLEDAI-2K ≥6 (n=10 031), the most common active manifestations were serological (89.8%), renal (72.9%), cutaneous (26.4%) and musculoskeletal (14.3%). In patient visits with an SLEDAI-2K <6 (n=32 314), renal (7.3%), cutaneous (6.7%), haematological (5.8%) and musculoskeletal (1.3%) disease activity were still present.Conclusion Serological, renal, cutaneous, musculoskeletal and haematological manifestations predominate in patients with active SLE; other organs are affected infrequently. Trial outcome measures could focus on measuring change in these systems and omit detailed analysis of rare events. Conversely, some patients with active disease in common domains would be ineligible for clinical trials based on an SLEDAI-2K <6. Use of organ-specific activity measures and inclusion criteria may overcome this limitation.